An Analytical Evaluation of the Signification of ‘The Development of Metaphysics in Persia’ in the Advancement of Allama Muhammad Iqbal’s Theo-Philosophic Ideas (Al-Qamar, 2024)
Allama Muhammad Iqbal (1877-1038) is a versatile thinker of the modern Muslim world. Although he was born in Sub-Continent but his thought crossed all the barriers of color, creed, race and land. Syed Jamal Din Afghani (1838-1898) was the 1st person who set the foundation of the renaissance of the modern Muslim world. Iqbal preceded and accelerated Syed Jamal al Din Afghani’s movement of reformation with his sagacious approach in a new way with new dimensions. He used both the mediums ‘prose’ and ‘poetry’ to present his thought. His poetic work is in Persian and Urdu languages while his prose work is in English, Urdu and Persian. He was a theologian, philosopher, mystic poet and politician. His 1st research work is his doctoral dissertation under the title ‘The Development of Metaphysics in Persia’.  This research work is the 1st outcome of his intellectual endeavors during his stay in Europe from 1905 to 1908 in England and Germany. A common viewpoint of Iqbal scholars about this research work of is that ‘it is outdated and has no value in Iqbal’s thought and literature now’. The last and final philosophical work of Allama Iqbal is under the title ‘The Reconstruction of Religious Thought in Islam’. From 1st to final philosophical work there are many others his valuable books in poetry and prose. In this article our aim is to analyze the said views about his doctoral thesis and to find out the significance of his 1st philosophical work in the development of his thought.
Keywords: Metaphysics; Development; Thought; Change; Theology; Philosophy; Sufism 1; Introduction